2015
DOI: 10.1128/jcm.01349-15
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Presence of Insertion Sequence Excision Enhancer and Insertion Sequence IS 629 Correlates with Increased Diversity and Virulence in Shiga Toxin-Producing Escherichia coli

Abstract: cAlthough new serotypes of enterohemorrhagic Escherichia coli (EHEC) emerge constantly, the mechanisms by which these new pathogens arise and the reasons emerging serotypes tend to carry more virulence genes than other E. coli are not understood. An insertion sequence (IS) excision enhancer (IEE) was discovered in EHEC O157:H7 that promoted the excision of IS3 family members and generating various genomic deletions. One IS3 family member, IS629, actively transposes and proliferates in EHEC O157:H7 and enteroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Pathogenome Architecture and Virulence Profiles of Stx (−) NSF O157:H7 and SF O157:NM Alterations in genome size and architecture in EHEC O157:H7/NM are driven by the individual prophage complement, particularly Stx-phages Eppinger et al, 2011b;Shaaban et al, 2016) and dynamics of other MGEs (Eppinger et al, 2011b;Yokoyama et al, 2011;Stanton et al, 2014;Toro et al, 2015). We compared the chromosomes of the Stx (−) NSF O157:H7 and SF O157:NM strains with BRIG (Alikhan et al, 2011) using Stx (+) strain EC4115 (stx1−, stx2a+, stx2c+) as reference (Eppinger et al, 2011b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pathogenome Architecture and Virulence Profiles of Stx (−) NSF O157:H7 and SF O157:NM Alterations in genome size and architecture in EHEC O157:H7/NM are driven by the individual prophage complement, particularly Stx-phages Eppinger et al, 2011b;Shaaban et al, 2016) and dynamics of other MGEs (Eppinger et al, 2011b;Yokoyama et al, 2011;Stanton et al, 2014;Toro et al, 2015). We compared the chromosomes of the Stx (−) NSF O157:H7 and SF O157:NM strains with BRIG (Alikhan et al, 2011) using Stx (+) strain EC4115 (stx1−, stx2a+, stx2c+) as reference (Eppinger et al, 2011b).…”
Section: Resultsmentioning
confidence: 99%
“…When compared to the 3072/96 pSFO157 reference plasmid (Brunder et al, 2006), we identified two InDel regions that account for the plasmid size difference of 2,078 bp, both of which are associated with IS elements (Supplementary Figure S7). Similar to the role of phages in microevolution and emergence of sublineages Eppinger et al, 2011b;Yokoyama et al, 2011;Stanton et al, 2014;Sanjar et al, 2015;Toro et al, 2015;Yin et al, 2015;, mobile elements are also major drivers of plasmid diversification and are responsible for the observed differences in pSFO157 plasmid size. InDel-1 is located within the boundaries of transposable element Tn2501 (Michiels et al, 1987) present in the LSU-61 and 3072/96 plasmids, though the LSU-61 variant is 400 bp larger (Supplementary Figure S7A).…”
Section: Plasmid Inventory Of Stx (−) Sf O157:nm and Nsf O157:h7 Strainsmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, an IS excision enhancer (IEE) element was discovered in EHEC O157 promoting the excision and deletion of IS3 family members, resulting in genomic rearrangements and strain diversification (44,45). In the strains analyzed, the IEE element (IEE cluster I) was present solely in O26 lineage 1, suggesting that these strains have a higher potential to increase their diversity and virulence than those of lineage 2 (46). IEE cluster I has been found in different pathogenic strains from diverse serotypes (O157:H7, O26:H11, O111:H11, O118:NM, O145:H28, and O139:NM/H38) that are frequently involved in serious outbreaks (2,47).…”
Section: E Coli O26:h11/hmentioning
confidence: 99%